Subbrow Blepharoplasty Combined with Periorbital Muscle Manipulation for Periorbital Rejuvenation in Asian Women. Issue 5 (November 2019) - Wang, Jianzhang; Su, Yingjun; Zhang, Juan; Guo, Peng; Song, Baoqiang
Abstract : Background: With advancing age, Asian women are often plagued by lateral hooding of the upper eyelid skin, eyebrow ptosis, and obvious periorbital wrinkles. The authors propose a novel technique to revive the natural eyelid shape with a stable eyebrow position and alleviate periorbital wrinkles in Asian women. Methods: Sixty-six patients underwent subbrow blepharoplasty combined with periorbital muscle manipulation. An ellipse shape of the skin and subcutaneous tissue below the eyebrow was measured, demarcated, and removed. Then, the orbicularis oculi muscle beneath the subcutaneous tissue was exposed and dissected at the upper third. The lower muscle flap was fixed to the supraorbital rim periosteum and the upper musculocutaneous flaps, forming a cross flap for interlocking fixation. The lateral border of the orbicularis oculi muscle was detached from the subcutaneous tissue, splayed out, and sutured upward and inward to the periosteum. The corrugator supercilii muscle temporal to the origin of the supraorbital nerve notch was separated by 1 to 2 mm. The operation results were evaluated by patient satisfaction and comparisons between preoperative and postoperative photographs. Results: Subbrow blepharoplasty combined with periorbital muscle manipulation significantly corrected lateral hooding with a stable eyebrow position and reduced the crow's feet and glabellar frown lines in all patients. The persistence of the improved outcome was stable during the follow-up period. Postoperative scarring was inconspicuous; however, eight cases had transient postoperative forehead numbness. Conclusions: This novel procedure provides a simple, effective, and comprehensive technique for improving periorbital aging in Asian women. The surgical outcomes are predictable, and the postoperative scarring is inconspicuous. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.